2019
DOI: 10.1159/000504364
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Clinical Allergy and Immunology 2019

Abstract: The immune system has vital functions for homeostasis and host defense. Thus, imbalances of the immune system whether associated with allergy, hypersensitivity, or autoimmunity are of great importance, as is manifest from common diseases such as atopic diseases, urticaria, and angioedema, and drug hypersensitivity reactions. These can affect patients’ quality of life and can generate high costs for health care. Epidemiological studies have provided evidence for changing patterns of allergic diseases caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 153 publications
1
26
0
Order By: Relevance
“…Allergies are a major health issue in developed countries, and there is currently no effective therapeutic strategy to cope with allergies. Allergy pathologies are associated with a breakdown of immune tolerance ( 127 ), microbiota dysbiosis ( 128 ) and an increase in epithelial permeability ( 129 ). They may be observed within the first month of life, suggesting the possibility of early childhood preprogramming these biological systems and possibly reducing the risk of allergy development.…”
Section: Hmos As a New Potential Therapeutic Agentmentioning
confidence: 99%
“…Allergies are a major health issue in developed countries, and there is currently no effective therapeutic strategy to cope with allergies. Allergy pathologies are associated with a breakdown of immune tolerance ( 127 ), microbiota dysbiosis ( 128 ) and an increase in epithelial permeability ( 129 ). They may be observed within the first month of life, suggesting the possibility of early childhood preprogramming these biological systems and possibly reducing the risk of allergy development.…”
Section: Hmos As a New Potential Therapeutic Agentmentioning
confidence: 99%
“…Diagnosis of food‐related anaphylaxis or Hymenoptera venom allergy should follow the same procedures described in the previous sections. In addition, baseline and acute serum tryptase levels should be determined since patients with severe anaphylaxis (grade IV) have significantly higher levels of tryptase than those with mild to moderate anaphylaxis 73 . Furthermore, an increase in serum tryptase values > 20% above baseline levels +2 μg/L serves as a biomarker for MC activation and is one of the criteria applied for MCAS diagnosis 74,75 …”
Section: Anaphylaxismentioning
confidence: 99%
“…In addition, baseline and acute serum tryptase levels should be determined since patients with severe anaphylaxis (grade IV) have significantly higher levels of tryptase than those with mild to moderate anaphylaxis. 73 Furthermore, an increase in serum tryptase values > 20% above baseline levels +2 μg/L serves as a biomarker for MC activation and is one of the criteria applied for MCAS diagnosis. 74,75 A study assessed 171 patients with a history of immediate reactions to β-lactams compared to 122 healthy controls, finding that a β-lactam-sIgE [hapten c1 (penicilloyl G), c2 (penicilloyl V), c5 (ampicilloyl), c6 (amoxicilloyl)] to tIgE ratio ≥ 0.002 had a positive predictive value of 92.5%, thus enabling the identification of genuinely reactive patients, even among individuals with high tIgE levels (>200 kU/L).…”
Section: Anaphylaxismentioning
confidence: 99%
“…Several studies have demonstrated that air contamination is closely related to emphysema and pulmonary fibrosis [ 28 ]. Allergy-prone patients who have more abundant and expressed IgE and FcεR receptors [ 29 ] may experience more significant inflammation and immune responses when exposed to airborne antigens. Furthermore, TGF-β1, for example, is known to play an major role in the differentiation of fibroblasts into myofibroblasts [ 30 ] and eosinophil-derived IL-13 is closely associated with emphysema [ 31 ].…”
Section: Discussionmentioning
confidence: 99%